Evaluation of Electronic Reference Sources - Singh, S.P. (DESIDOC Journal of Library & Information Technology, 2003)
Discusses the impact and acceptability of information technology (IT) in libraries and information centres. Mentions how the role of reference librarian is changing with the change in the mode of production and access to reference sources in the libraries. It also adds what is expected of reference librarian to face the challenges of today. Emphasizes the need of knowing how to evaluate CD-ROMs and online reference sources, enumerates the important characteristics of reference sources, finally describes in detail various criteria which can be used for evaluation of e-sources. http://dx.doi.org/10.14429/dbit.23.2.3596